Visitantes florais e dispersão de Symplocos uniflora (Pohl) Benth. (Symplocaceae) em três Unidades de Conservação do Rio Grande do Sul - Goetz, Kerolin Frison (2023)
Symplocos is a genus of the Symplocaceae family with 318 species, 45 of which are known. currently in Brazil, one of them is Symplocos uniflora. S. uniflora is a tree species, native of Brazil with occurrence in the South and Southeast, in the Cerrado and Atlantic Forest biomes. are described in the literature currently two genera of bees as pollinators, Trigona and Melipona, and as Dispersers are described two arboreal mammals, Didelphis aurita and Guerlinguetus ingrami. This study aimed to analyze the phenology and morphology of Symplocos uniflora, complement data on pollination and identify species of birds that feed and disperse the fruits, filling an important information gap about the interaction of birds with the species, mainly for Rio Grande do Sul. The study was carried out in three Conservation Units in Rio Grande do Sul, including the Aracuri Ecological Station, Esmeralda, located in the northeast of the State and Passo Fundo National Forest and Reserve Private National Heritage University of Passo Fundo, located in the north of the State, where three individuals of S. uniflora were selected per study area. Related studies to pollination presented a total of 599 individuals of floral visitors distributed across 18 species, with Hymenoptera and Lepdoptera being the orders with the largest number of species, with Apis mellifera the most representative visitor with 433 visits. The richness and abundance of species does not varied significantly between the areas studied. Regarding seed dispersal, there were four species were observed feeding on the fruits, namely Turdus rufiventris (Sabiálaranjeira), Turdus subalaris (Blacksmith Thrush), Zonotrichia capensis (Tico-tico) and Sus scrofa (Boar), being sampled only in Esec Aracuri-Esmeralda. The results obtained during the study demonstrate that Apis mellifera is a potential effective pollinator for S. uniflora, in addition the species of pollinators already known; in relation to dispersal, Turdus species are effective dispersers for S. uniflora.